The Resilience of LGBTQIA Students on Delhi Campuses - Krishan, Anjali; Rastogi, Apurva; Singh, Suneeta; Malik, Lakshita (World Bank, Washington, DC, 2015)
This study finds that college-going Lesbian Gay Bisexual Transgender Queer Intersex Asexual (LGBTQIA) persons on Delhi campuses face a highly discriminatory context of adversity, which makes their desired outcome for acceptance virtually impossible to achieve. Using the mixed-methods resilience research approach, this project examines how they negotiate through these challenges to reach some approximation of acceptance in their lives. The study aims to gain a better understanding of the issues that persons who identify as LGBTQIA face, the resilience strategies that enable respondents, and how the costs of these resilience strategies are negotiated. It covers the following five thematic areas: (1) understanding what acceptance means for respondents, and how they try to navigate towards it; (2) charting the types of discrimination and stigma that respondents face in their educational environment; (3) identifying the resources and support networks respondents use to cope with discrimination and what, if any, consequences accompany their use; (4) determining the impact of protective and promotive resilience strategies on the context of adversity and the gaining of acceptance; and (5) exploring how respondentss fears and hopes for their futures evolve during higher education. The study finds that while respondents use multiple resilience strategies to carve out a space where they belong and find acceptance, these strategies are costly. The costs are born out of and reinforce the stigma and discrimination against LGBTQIA prevalent in Indian society. Individuals and the LGBTQIA community on Delhi campuses have thus had to strategically navigate their environment to modulate these costs. Our research indicates that these strategies can in turn be used to alter the context of adversity for LGBTQIA students on Delhi campuses.